Analisis Konten Dakwah pada Akun Youtube Bale Films Edisi Diary Ramadhan 2018 - Naning Nuraliah; Chodidjah Makarim; Santi Lisnawati (Da'watuna: Journal of Communication and Islamic Broadcasting, 2022)
This study discusses the analysis of da'wah content on the bale films YouTube account diaryramadhan 2018 edition. The purpose of this study is to determine the content of da'wah messages contained in the Bale Films YouTube account, the strategy for presenting da'wah messages contained in the account and to determine the communication process of da'wah messages. on Bale Films' YouTube account. This research focuses on da'wah contained in da'i, mad'u, methods, messages and media. This study uses the S-M-C-R theory or often called the Berlo Model theory to answer the problem. The method used by the researcher is the method of content analysis. This method is used to analyze, explain, understand and describe the problems that exist in the research. The steps taken in this research are to determine the type of data, data sources, data collection techniques, analyze to answer all the problems that exist in the research. The results of the study explain that the message of da'wah delivered through video is sourced from the Al-Quran and As-Sunnah. The message of da'wah is divided into messages of faith, messages of sharia as well as messages of morality. The message of da'wah that is most widely uploaded is the message of morality. The strategy for presenting the da'wah message is using YouTube's social media, the presentation is in the form of a message of kindness wrapped in a video in which there are several elements of da'wah which also has educational and comedy values ​​to make it easier to accept. Then the communication process is carried out by using the da'wah bil Lisan method. This method also provides the opportunity for mad'u to be able to determine the message of da'wah according to their abilities and interests so that the purpose of da'wah communication is effective and efficient. Keywords : Communication, Da'wah, Social Media, YouTube.